AN ANALYSIS OF SPEECH ACT IN ELEMENTAL:FORCES OF NATURE (2023) MOVIE SCRIPT - Melani Sharifah; Muh Shofiyuddin (IKIP Siliwangi, 2024)
Pragmatic is a branch of linguistics which concentrates on language use. Speech acts are one of the learning domains under pragmatics. In this research, the researcher will find out the speech acts contained in the movie of Elemental:Forces of Nature. This research focus on the types of illocutionary acts that found in the utterances spoken by the film actors, namely declarative act, expressive act, directive act, commissive act and assertive act. The descriptive qualitative method was employed in this research. Data sources were obtained through observation and documentation. Researchers obtained data through watching the movie, reading the script, taking note of the utterances, classifying and identifying the types of illocutionary acts based on the data display. Researchers found there were 213 utterances that were included in the illocutionary types. The results found by the researchers were declaration types with 3%, expressive acts with 29%, directive acts with 34%, commissive acts with 7% and assertive acts with 27%. The dominant speect act in this movie is the directive act with a percentage of 34% and the least is the declarative act with 3%.